(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Pedagogical skill of a music teacher is to organize all forms of the educational process in the most convenient and effective way, to direct them towards the goals of personal development, to form the ability of musical and spiritual worldview in students, necessary for society. It is considered one of the main tasks to arouse a tendency to activity. This article also addresses the same issues.